Smallholder farmers' information behavior differs for organic versus conventional pest management strategies: A qualitative study in Uganda. (1st June 2020) - Diemer, Nikola; Staudacher, Philipp; Atuhaire, Aggrey; Fuhrimann, Samuel; Inauen, Jennifer
Abstract: Conventional pesticides are associated with numerous human and environmental health risks. Nevertheless, an increasing number of smallholder farmers in low- and middle-income countries are using conventional pesticides. Adopting safer pest management requires farmers to obtain new information. However, little is known how farmers develop an information need, seek, and use pest management related information, and whether this process differs for organic and conventional pest management strategies. In this qualitative study, we investigated pest-related information behavior in depth, from farmers' own perspective. Using an ethnographic approach, we conducted 46 semi-structured interviews, 15 on-farm observations and 302 structured questionnaire interviews with farmers in Wakiso District, Uganda, in 2017. Our results indicated that farmers develop information needs when adopting new farming practices, or when presented with disruptive information (e.g. when new pests emerged). This prompted farmers to seek information actively, or they received passive information. Whether farmers used the new information depended on successful trial of the new pest management strategy, and on the credibility of the source. Most revealing, our results suggested important differences in information behavior between conventional and organic pest management strategies. Sources of information for conventional pesticides were well-integrated into farmers' daily lives and comprised pesticide dealers and fellow farmers. Conversely, information on organic strategies was provided through external sources (e.g. NGOs), and was not available at times when farmers developed an information need. Our results imply that farmers are most likely receptive to organic pest management information at times when they develop an information need (e.g. when encountering a new pest). To promote safer pest management, information about organic and integrated pest management should be made continuously available in farmers' lives. Furthermore, we recommend leveraging established information channels (e.g. dealers) among pesticide users to promote safer use practices. Highlights: Farmers use different information sources depending on pest management strategy. Information about conventional pesticides is locally embedded. Organic pest management information isn't easily accessible in farming communities. We recommend promoting safe pesticide use through established channels.